2005 IEEE Congress on Evolutionary Computation
DOI: 10.1109/cec.2005.1555047
|View full text |Cite
|
Sign up to set email alerts
|

DynDE: a Differential Evolution for Dynamic Optimization Problems

Abstract: This paper presents an approach of using Differential Evolution (DE) to solve dynamic optimization problems. Careful setting of parameters is necessary for DE algorithms to successfully solve optimization problems. This paper describes DynDE, a multi-population DE algorithm developed specifically to solve dynamic optimization problems that doesn't need any parameter control strategy for the F or CR parameters. Experimental evidence has been gathered to show that this new algorithm is capable of efficiently sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
151
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(151 citation statements)
references
References 4 publications
0
151
0
Order By: Relevance
“…An effective method of tracking all optima is to maintain several independent sub-populations of DE individuals, one sub-population on each optimum. In their most successful experiments Mendes and Mohais [19] used 10 subpopulations, each containing 6 individuals.…”
Section: Multiple Populationsmentioning
confidence: 99%
See 4 more Smart Citations
“…An effective method of tracking all optima is to maintain several independent sub-populations of DE individuals, one sub-population on each optimum. In their most successful experiments Mendes and Mohais [19] used 10 subpopulations, each containing 6 individuals.…”
Section: Multiple Populationsmentioning
confidence: 99%
“…Use of Brownian individuals involves the creation of individuals close to the best individual by adding a small random value, sampled from a normal distribution, to each component of the best individual. Mendes and Mohais [19] adapted the ideas from Blackwell and Branke [3] to create their multi-population algorithm, DynDE, which uses exclusion to prevent populations from converging to the same peak. Mendes and Mohais [19] showed that DynDE was at least as effective as its PSO based counterparts.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations